The quality of bilateral trade between Chile and Peru: a research proposal - Cornejo Ramírez, Enrique Javier (2022)
This article analyzes the quality of bilateral trade between Chile and Perú, starting from a conceptual proposal: that this trade will be of quality if four keys factors show a good performance: growth of the mutual flows of exports and imports, structure of that trade, degree of diversification of the tourist flows between the two countries and behavior of the direct investment that each country makes in the other. The analysis carried out reviews the historical background of the aforementioned commercial relationship and then analyzes in detail the four factors mentioned, concluding that bilateral trade is of quality, due to the positive concurrence of three of the four indicators.